Revolution and Literature: Russian Writers Literary Sociology of Revolution: The Specious Paradoxical Relationship between Literature and Revolution - Mehdi Najafzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The relationship between revolution and literature can be traced during three distinctive stages. In the first stage which is before the time that revolution stabilizes itself, the literature definitely assists the revolution and spreads the revolutionary slogans. When it comes to the second stage, during the consolidation of the revolution, the revolutionaries deny the independent literature. And finally, in the third stage, literature tries to move to the hidden transcript of society against the obstacles of the political hegemony and departs form revolution and its slogans. The “regulation and literature” book, which is a trilogy by Jürgen Ruhle, has explained this paradoxical relationship. This trilogy is a critical study of the literature and communism in the twentieth century. In the first book Ruhle described the sodality and opposition between the Russian authors and October Revolution. In the second book, he emphasized German literature especially Marxist works from 1917 to 1960, and in the third book, the focus was on the Marxist works in Latin America. In the current paper, we try to explain the contradictory relationship between literature and revolution with emphasis on this trilogy. We especially focus on “Revolution and Literature: Russian Writers” book and use new approaches such as Bakhtian formalism, new literary criticism, and trans-historical theory.